ANALISIS PERAWATAN KENDARAAN PKP-PK DALAM MENUNJANG KESELAMATAN PENERBANGAN DI BANDAR UDARA SULTAN BABULLAH TERNATE - Besi, Balgis S. Ode; Rachmawati, Desiana (Yayasan Education and Social Center, 2024)
Based on the Regulation of the Director General of Civil Aviation KP 14 of 2015, every airport must have a certificate with ARFF facilities according to the category for flight safety. This certificate requires regular maintenance of ARFF vehicles, including oil and filter changes. The ARFF unit is responsible for handling accident and fire incidents with a quick response time. The purpose of this research is to analyze the maintenance activities of PKP-PK vehicles in supporting flight safety at Sultan Babullah Ternate Airport. This study uses a qualitative approach to explore and understand social and human issues related to ARFF vehicle maintenance. Data was collected through interviews with the head of the unit and two ARFF officers, direct observation, and documentation with the ARFF Unit at Sultan Babullah Ternate Airport, in May 2024. Then it was analyzed using a qualitative descriptive method. The analysis results show that the ARFF vehicle maintenance procedures at Sultan Babullah Ternate Airport include routine daily, weekly, monthly, semester, and post-extinguishing activities according to SOPs. Challenges such as shortages of spare parts and budget delays hinder maintenance, which is essential for maintaining vehicle performance and flight safety. Simulations are conducted to improve the performance and response of officers according to AEP, supporting aviation security and safety